2011
DOI: 10.1016/j.ajpath.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Microarray Cytometry Reveals Positive Impact of Homeodomain Interacting Protein Kinase 2 in Colon Cancer Survival Irrespective of p53 Function

Abstract: The human p53 gene is a tumor suppressor mutated in half of colon cancers. Although p53 function appears important for proliferation arrest and apoptosis induced by cancer therapeutics, the prognostic significance of p53 mutations remains elusive. This suggests that p53 function is modulated at a posttranslational level and that dysfunctions affecting its modulators can have a prognostic impact. Among p53 modulators, homeodomain interacting protein kinase (HIPK) 2 emerges as a candidate "switch" governing p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…It was recently shown that changes in the expression levels of HIPK2 between the normal and tumor tissue of each colorectal carcinoma patient have a positive effect on survival, irrespective of p53 function, raising the possibility of a p53‐independent apoptotic modulation 33. However, this study found no significant difference in the range of expression level in the tumors compared with the normal mucosa or in a subgroup of tumors 33…”
Section: Discussioncontrasting
confidence: 70%
“…It was recently shown that changes in the expression levels of HIPK2 between the normal and tumor tissue of each colorectal carcinoma patient have a positive effect on survival, irrespective of p53 function, raising the possibility of a p53‐independent apoptotic modulation 33. However, this study found no significant difference in the range of expression level in the tumors compared with the normal mucosa or in a subgroup of tumors 33…”
Section: Discussioncontrasting
confidence: 70%
“…We found that HIPK2 expression markedly decreased in invasive carcinomas, whereas it was highly expressed in preinvasive lesions. In addition, Soubeyran et al 19 has shown that the increased expression of the HIPK2 protein in colorectal tumor cells compared with paired normal tissue cells has a strong impact on better survival in patients with colorectal cancer. DOrazi et al 18 also reported that HIPK2 knockdown strongly correlates with increased tumor growth in colorectal cancer in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…DOrazi et al 18 also reported that HIPK2 knockdown strongly correlates with increased tumor growth in colorectal cancer in vitro. In addition, Soubeyran et al 19 has shown that the increased expression of the HIPK2 protein in colorectal tumor cells compared with paired normal tissue cells has a strong impact on better survival in patients with colorectal cancer. The authors concluded that HIPK2 depletion is associated with tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNAs were used to determine p53 mutational status by sequencing, while RNA extracts were used to quantify p21 transcript levels by qRT-PCR. 14 The TMA was done to contain one core of normal mucosa (punched far away JNK/p38 kinases (as proposed above) were supposedly induced. It is still puzzling to understand why and how HIPK1 specifically targets serine 15.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies implicate HIPK1 in carcinogenesis, but it is still difficult to assign a pro-or anti-tumoral role to it, and even more to find convincing in vivo data. To fill this gap, we used a TMA (previously generated in our laboratory), 14 composed of both normal and tumoral tissue from 80 colorectal cancer (CRC) patients, and compared HIPK1 expression levels in each type of sample after immunohistochemical staining (Fig. 1A-C).…”
Section: Hipk1mentioning
confidence: 99%